Characterization of hand forces exerted during non-powered hospital bed pushing and pulling tasks. Issue 2 (3rd April 2022) - Leban, Bruno; Fabbri, D.; Lecca, L. I.; Uras, M.; Monticone, M.; Porta, M.; Pau, M.; Campagna, M.
Abstract : Accurate assessment of biomechanical risk associated with pushing/pulling tasks represents a challenging issue, especially in the health system where personnel are often required to maneuver beds and carts. Most studies in this field have been carried out in the laboratory, while few data have been collected under actual working conditions. This study aims to characterize the forces exerted during non-powered hospital bed maneuvering. Twenty participants were required to move a bed (equipped with a customized handlebar to measure exerted forces) along an actual hospital path including straight, turn and maneuver phases. The results show that higher forces are associated with the initial phase (peak and mean values 222 and 68 N) while the straight, turn and maneuvering phases required similar (lower) efforts. The combined effect of left, right and transversal forces suggests that the trunk of the operator might experience axial rotation, thus calling for further investigations of this aspect.